2020
DOI: 10.1088/2053-1583/ab834b
|View full text |Cite
|
Sign up to set email alerts
|

Interface chemistry and thermoelectric characterization of Ti and TiOx contacts to MBE-grown WSe2

Abstract: WSe2 has demonstrated potential for applications in thermoelectric energy conversion. Optimization of such devices requires control over interfacial thermal and electrical transport properties. Ti, TiOx, and Ti/TiOx contacts to the MBE-grown WSe2 are characterized by XPS and transport measurements. The deposition of Ti is found to result in W-Se bond scission yielding metallic W and Ti-Se chemical states. The deposition of Ti on WSe2 in the presence of a partial pressure of O2, which yields a TiOx overlayer, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The initial conditions are chosen to match the experiments. 28,29 The electronic subsystem is pumped at 400 nm, corresponding to ∼3.1 eV. The 3.1 eV of energy is distributed between the electron and the hole.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial conditions are chosen to match the experiments. 28,29 The electronic subsystem is pumped at 400 nm, corresponding to ∼3.1 eV. The 3.1 eV of energy is distributed between the electron and the hole.…”
Section: Resultsmentioning
confidence: 99%
“…2, majority of the carriers are excited from around this energy, and the symmetrical initial condition provides a better representation of the experiments. 28,29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The base pressure during the sputtering process (≈10 −3 mbar) is actually resulting in Ti metal and TiO x deposition, instead of pure Ti metal. [ 20 ] The P and In atoms are seen diffused into the Al 2 O 3 layer slightly after PMA at 400 °C, resulting in an intermixing region near the InP/Al 2 O 3 interface. Besides, the intermixing region is also seen at the Ti/Al 2 O 3 interface.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the TBC depends on the details of the contact, and the level of oxidization of titanium and is in the range of 6 to 22 MW/m 2 K. Despite the small thermal conductance values, the studied interface has a low ZT due to the dominance of the electronic tunneling transport. [247] A few experiments have been conducted to measure the cross-plane Seebeck coefficient of 2D heterostructures. Chen et al [215] stacked a Gr/hBN/Gr heterostructure and patterned electrodes on the top and bottom graphene sheets.…”
Section: Cross-plane Transport: Solid-state Thermionic Structurementioning
confidence: 99%